An ADP-Ribosylation Factor GTPase-activating Protein Git2-short/KIAA0148 Is Involved in Subcellular Localization of Paxillin and Actin Cytoskeletal Organization - Mazaki, Yuichi (The American Society for Cell Biology, 2001)
Paxillin acts as an adaptor protein in integrin signaling. We have shown that paxillin exists in a relatively large cytoplasmic pool, including perinuclear areas, in addition to focal complexes formed at the cell periphery and focal adhesions formed underneath the cell. Several ADP-ribosylation factor (ARF) GTPase-activating proteins (GAPs; ARFGAPs) have been shown to associate with paxillin. We report here that Git2-short/KIAA0148 exhibits properties of a paxillin-associated ARFGAP and appears to be colocalized with paxillin, primarily at perinuclear areas. A fraction of Git2-short was also localized to actin-rich structures at the cell periphery. Unlike paxillin, however, Git2-short did not accumulate at focal adhesions underneath the cell. Git2-short is a short isoform of Git2, which is highly homologous to p95PKL, another paxillin-binding protein, and showed a weaker binding affinity toward paxillin than that of Git2. The ARFGAP activities of Git2 and Git2-short have been previously demonstrated in vitro, and we provided evidence that at least one ARF isoform, ARF1, is an intracellular substrate for the GAP activity of Git2-short. We also showed that Git2-short could antagonize several known ARF1-mediated phenotypes: overexpression of Git2-short, but not its GAP-inactive mutant, caused the redistribution of Golgi protein β-COP and reduced the amounts of paxillin-containing focal adhesions and actin stress fibers. Perinuclear localization of paxillin, which was sensitive to ARF inactivation, was also affected by Git2-short overexpression. On the other hand, paxillin localization to focal complexes at the cell periphery was unaffected or even augmented by Git2-short overexpression. Therefore, an ARFGAP protein weakly interacting with paxillin, Git2-short, exhibits pleiotropic functions involving the regulation of Golgi organization, actin cytoskeletal organization, and subcellular localization of paxillin, all of which need to be coordinately regulated during integrin-mediated cell adhesion and intracellular signaling.